Understanding Uncertainties in Supply Chain when Outsourcing Manufacturing Operations to China - Xu, Wenjing (2006)
This paper describes the uncertainties in supply chain when western companies outsourcing manufacturing operations to china. A large amount of uncertainties could happen in supply chain and they are divided into 3 groups including supply uncertainties, process uncertainties and demand uncertainties. The survey aims to identify what uncertainties most frequently occur in supply chain, what kinds of activities have been taken to reduce uncertainties and whether these activities are effective in practice. According to the survey result, this paper provides some recommendations on how to lessen those frequent uncertainties in supply chain as well. The findings show that uncertainties most concerned by western outsourcing companies are lack of quick response, long order-cycle time, quality problems and delivery delays, while in the eyes of Chinese supplier, it could be demand changes and transport uncertainties. Some activities, like quality control techniques, are effective in solving certain uncertainties while others are not. It is necessary for both Chinese suppliers and western companies to take more efforts on better control of supply chain uncertainties.